2023
DOI: 10.1002/cncr.34698
|View full text |Cite
|
Sign up to set email alerts
|

TET2 and LILRB1 mutations are frequent in Epstein–Barr virus‐positive diffuse large B‐cell lymphoma especially in elderly patients

Abstract: Background Diffuse large B‐cell lymphoma (DLBCL) harboring Epstein–Barr virus (EBV) primarily occurs in patients who have underlying immunodeficiency or in elderly patients but is also reported in young, immunocompetent patients. The authors investigated the pathologic differences in EBV‐positive DLBCL in these three groups of patients. Methods In total, 57 patients with EBV‐positive DLBCL were included in the study; of these, 16 patients had associated immunodeficiency, 10 were young (younger than 50 years), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…However, in vivo studies have shown that the expression of LMP1 or LMP2A alone cannot lead to malignant transformation of B cells, and the activity of BTK pathway in EBV+DLBCL-NOS tumor cells is significantly down-regulated [ 26 ]. A large number of pathogenic mutations were also detected in EBV+DLBCL-NOS ( Table 2 ) [ 9 , 27 , 28 ]. For example, Liu et al analyzed 11 Chinese patients with EBV+DLBCL-NOS using whole exome sequencing [ 7 ].…”
Section: Molecular Features Of Ebv+dlbcl-nosmentioning
confidence: 99%
“…However, in vivo studies have shown that the expression of LMP1 or LMP2A alone cannot lead to malignant transformation of B cells, and the activity of BTK pathway in EBV+DLBCL-NOS tumor cells is significantly down-regulated [ 26 ]. A large number of pathogenic mutations were also detected in EBV+DLBCL-NOS ( Table 2 ) [ 9 , 27 , 28 ]. For example, Liu et al analyzed 11 Chinese patients with EBV+DLBCL-NOS using whole exome sequencing [ 7 ].…”
Section: Molecular Features Of Ebv+dlbcl-nosmentioning
confidence: 99%
“…Therefore, blockade of the PD-1/PD-L1 axis may enhance an antitumor immunity of both adaptive and innate mechanisms. Of note, the receptors PD-1, LILRB1, and SIRPa all contain an immunoreceptor tyrosine-based inhibitory motif domain, which may be instrumental for downstream signals that inhibit phagocytosis (258, 259,274,276,277). Based on this, in studies aimed at monitoring response in patients with cancer undergoing treatment with immune checkpoint inhibitors, researchers should consider the myeloid compartment as a potential target and predictive biomarker (104,160).…”
Section: Other Checkpoint Signaling Pathwaysmentioning
confidence: 99%
“…Of note, the receptors PD-1, LILRB1, and SIRPα all contain an immunoreceptor tyrosine-based inhibitory motif domain, which may be instrumental for downstream signals that inhibit phagocytosis ( 258 , 259 , 274 , 276 , 277 ). Based on this, in studies aimed at monitoring response in patients with cancer undergoing treatment with immune checkpoint inhibitors, researchers should consider the myeloid compartment as a potential target and predictive biomarker ( 104 , 160 ).…”
Section: Tam-targeted Therapiesmentioning
confidence: 99%